Editorial - Lăcrămioara STOICU-TIVADAR; Parisis GALLOS; Sorana D. BOLBOACĂ (Applied Medical Informatics)
The current special issue of the Applied Medical Informatics journal comes out with 14 papers as extended abstracts of the posters presented during the EFMI-STC 2024 conference “Collaboration across disciplines for the health of people, animals, and ecosystems”, 27-29 November 2024, Timişoara, Romania. This issue content has been peer-reviewed and edited by Medical Informatics scientists and researchers across the world. This event was organized by the Romanian Society of Medical Informatics, as a national member of the European Federation for Medical Informatics and hosted by University Politehnica Timişoara. West University Timişoara and “Victor Babeş” University of Medicine and Pharmacy Timişoara were co-organizers.